2001
DOI: 10.4141/s00-034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green manures on soil organic matter and wheat yields and N nutrition

Abstract: N' Dayegamiye, A. and Tran, T. S. 2001. Effects of green manures on soil organic matter and wheat yields and N nutrition. Can. J. Soil Sci. 81: 371-382. A field study was conducted for 5 yr (1993)(1994)(1995)(1996)(1997) to evaluate the effects of green manure residues applied to the soil in 1993 and 1995, on wheat (Triticum aestivum L.) yields and N nutrition as subsequent crop in 1994, 1996 and 1997. The effect of green manure application was also evaluated on soil microbial activity (CO 2 ), on C and N con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 28 publications
(41 reference statements)
6
27
1
1
Order By: Relevance
“…That led to increase SOM accumulation because of the slow decomposition of alfalfa green manure. Similar results were reported by (N'Dayegamiye and Tran, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That led to increase SOM accumulation because of the slow decomposition of alfalfa green manure. Similar results were reported by (N'Dayegamiye and Tran, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Legumes are superior green manure c rops as they fix atmos pheric nitrogen and add it to the soil nitrogen pool. That nitrogen is releas ed gradually with long-term decomposition of organic matter, thus decreasing the risk of leaching nutrients and t he need for nitrogen fertilizer application in subs equent seasons (Leinonen, 2000;Mayer et al, 2003;N'Dayegamiye and Tran, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Weinert et al [10], GMS can provide to the following crop between 20% and 55% of their N fertilizer requirements [10]. However, the ability of GMs to release N depends on their chemical composition, including the C: N ratio, and lignin and polyphenol contents, and on environmental conditions such as soil moisture and temperature [11,12]. Furthermore, the N supply from GMS varies depending on its yield and N content [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability of GMs to release N depends on their chemical composition, including the C: N ratio, and lignin and polyphenol contents, and on environmental conditions such as soil moisture and temperature [11,12]. Furthermore, the N supply from GMS varies depending on its yield and N content [3,12]. To maximize the N use efficiency while minimizing the N loss, the amount and the timing of N release from GMS must be synchronized with the subsequent potato N needs for maximum tuber yields [13].…”
Section: Introductionmentioning
confidence: 99%
“…In Montana, legume plough-down had a greater effect on a low fertility soil than a high fertility soil (Westcott et al 1995). In Quebec, N'Dayegamiye andTran (2001) reported that green manures accounted for 25Á31% of total N uptake in the subsequent wheat crop, and suggested that plough-down in late summer or early autumn allowed for better synchrony with the N needs of the crop.…”
mentioning
confidence: 99%